Anonymously yours (Academic Video Online, 2003)
Every few years a new documentary comes along whose impact is so powerful, so illuminating, and so memorable that it is deemed an instant classic and an essential classroom teaching tool. "Anonymously Yours" is such a film. This extraordinary documentary on sex-trafficking in Southeast Asia interweaves four young women's stories to reveal an institution that enslaves as many as 40 million women worldwide. Shot clandestinely in Myanmar (formerly Burma), "Anonymously Yours" is often shocking, frequently harrowing, and always compelling. Through the brutal honesty of the four women's stories the film exposes the commonplace bartering and selling of women and the cycles of poverty that enslave them. From the back rooms of teashops and restaurants to the lounges of five-star hotels, the Far East sex trade thrives on the routine merchandising of girls and women for the sexual escape and pleasure of men from all cultures. Through their unforgettable and poignant testimonies, these four sex workers introduce Western audiences to the widespread corruption and staggering poverty that are the status quo in much of the world -- and the primary causes behind one of the fastest-growing and most vicious industries on earth: the sale of human beings."Anonymously Yours" will engage and challenge students and provoke animated discussion in a wide range of courses in women's studies, cultural anthropology, Asian studies, human rights, economics, and development issues. It was produced by Gayle Ferraro, who also produced the widely acclaimed documentary, "Sixteen Decisions."